EnLight - Lim, Alvin Jing Jie (2017)
Batteries are so readily available in our everyday lives but have we ever questioned ourselves the over reliance we have on them and the impact that might bring? More importantly, we should also spare a thought for the poverty-stricken at a shockingly 90% of the world’s population. Strongly inspired by the Design for the Other 90% movement, this project explores and highlights the inter-relatedness between the ethics of battery usage and an alternative energy that could possibly aid everyone in terms of emergency, especially in regions of flood-prone areas.